2009
DOI: 10.1007/bf03256157
|View full text |Cite
|
Sign up to set email alerts
|

The cost effectiveness of home-based provision of antiretroviral therapy in rural Uganda

Abstract: Context-Highly active anti-retroviral therapy (ART) provides dramatic health benefits for HIVinfected individuals in Africa, and widespread implementation of HAART is proceeding rapidly. Little is known about the cost and cost-effectiveness of HAART programs.Objective-To determine the incremental cost-effectiveness of a home-based HAART program in rural Uganda.Design, setting and patients-Computer-based, deterministic cost-effectiveness model to assess a broad range of economic inputs and health outcomes. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Several studies have shown the cost-effectiveness of HIV linkage and retention in care programs implemented in the USA (Creese, Floyd, Alban, & Guinness, 2002;Hogan, Baltussen, Hayashi, Lauer, & Salomon, 2005;Holtgrave, 1998;Kim et al, 2015;Losina et al, 2009;Marseille et al, 2009Marseille et al, , 2012Renaud, Basenya, De Borman, Greindl, & Meyer-Rath, 2009;Walker, 2003). The evaluators of Health Resources and Services Administration's Special Projects of National Significance found program costs of $241,565 ($393 per patient) (Gopalappa, Farnham, Hutchinson, & Sansom, 2012).…”
mentioning
confidence: 95%
“…Several studies have shown the cost-effectiveness of HIV linkage and retention in care programs implemented in the USA (Creese, Floyd, Alban, & Guinness, 2002;Hogan, Baltussen, Hayashi, Lauer, & Salomon, 2005;Holtgrave, 1998;Kim et al, 2015;Losina et al, 2009;Marseille et al, 2009Marseille et al, , 2012Renaud, Basenya, De Borman, Greindl, & Meyer-Rath, 2009;Walker, 2003). The evaluators of Health Resources and Services Administration's Special Projects of National Significance found program costs of $241,565 ($393 per patient) (Gopalappa, Farnham, Hutchinson, & Sansom, 2012).…”
mentioning
confidence: 95%
“…It is likely that the decrease in opportunistic infections and hospitalization and the improvement in clinical status had a positive economic impact on patients and their families due to their improved overall functioning possibly allowing for more time for employment and other productive economic activities. This has been the case in other studies that have examined cost-effectiveness of treatments to improve the health of patients with HIV [26, 27]. In this study, the factor was not measured because we considered only the perspective of the MINSA, the caregivers, and HCI.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ART was estimated to avert 7.3 discounted DALYs among HIV-infected individuals who survived >16 weeks. This value was drawn from the same Zambian analysis used to estimate treatment costs, and it was obtained by comparing deaths in the Zambian ART program with deaths observed in a prior, well-characterized home-based AIDS care (HBAC) cohort of 466 HIV-infected patients not receiving ART in Tororo District, Uganda, adjusted for differences in CD4+ T-cell counts and sex distribution between groups [16,19,24,25]. …”
Section: Methodsmentioning
confidence: 99%